2008
DOI: 10.1093/ajcn/87.1.212s
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic response and health: summary of a workshop

Abstract: Interest in the glycemic impact of diet on health and well-being is growing among health care professionals and consumers. Diets with high glycemic impact have been postulated to increase risk of obesity, insulin resistance, diabetes, and cardiovascular disease. A reduction in the glycemic impact of the diet has been proposed as a means of assisting body weight management, improving blood glucose control, and reducing diabetic, cardiovascular, and related risks. Foods are increasingly carrying labels that desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 8 publications
3
45
0
4
Order By: Relevance
“…This leads to a reduction in detoxification of ROS, resulting in lipid-, protein-, and DNA-peroxidation, and, finally, apoptosis (Rains and Jain, 2011). Glycated hemoglobin (HbA1c) is a good marker for diagnosis and prognosis of complications in diabetes, such as retinopathy, nephropathy, and neuropathy (Howlett and Ashwell, 2008). For example, it was shown that reduction of HbA1c by only 1 unit (8-7%) can reduce the risk of retinopathy by over 30% (Kowluru and Chan, 2007).…”
Section: Resveratrol and Oxidative Markersmentioning
confidence: 99%
“…This leads to a reduction in detoxification of ROS, resulting in lipid-, protein-, and DNA-peroxidation, and, finally, apoptosis (Rains and Jain, 2011). Glycated hemoglobin (HbA1c) is a good marker for diagnosis and prognosis of complications in diabetes, such as retinopathy, nephropathy, and neuropathy (Howlett and Ashwell, 2008). For example, it was shown that reduction of HbA1c by only 1 unit (8-7%) can reduce the risk of retinopathy by over 30% (Kowluru and Chan, 2007).…”
Section: Resveratrol and Oxidative Markersmentioning
confidence: 99%
“…Fibers convert intestinal contents into gel‐like substance that retard enzymatic activity on starch, thereby resulted into low GI (Oh et al., 2005). Howlett and Ashwell (2008) reported that low GI foods improve glycemic control by lowering glycated end‐products and improving insulin sensitivity. However, GI does not measure the quantity of carbohydrate, but its quality (Foster‐Powell, Holt, & Brand‐Miller, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Существуют исследования, указыва-ющие на успокаивающее действие сахарозы и снижение болевой чувствительности у детей в отличие от взрослых [28][29][30]. Есть основания полагать, что сладкие продук-ты могут усиливать восприятие образов и запоминание новых слов детьми раннего возраста [31,32].…”
Section: роль сахара в питании детейunclassified